Edukasi Protokol Kesehatan 3 M Sebagai Upaya Pencegahan Covid 19 Di SDN Inti Tondo Kecamatan Mantikulore Kota Palu Sulawesi Tengah - Pitriani Pitriani; Kiki Sanjaya; Riri Suwahyuni; Jamaluddin Jamaluddin (universitas wiralodra, 2021)
Early in 2021, after the discovery of vaccines covid - 19 discourse to school as usual had planned back, this can increase the potential of the students contracted the virus if it can not implement the health protocol 3 M (wear a mask, wash your hands and keep your distance) properly. Dedication to the community at Inti Tondo Elemtary School in Palu City done through counseling and practice protocols 3 M, this event was held on Saturday June 11th 2021 followed by second grade students as many as 22 people. The number of participants is limited since school schedule performed in rotation during a pandemic. Activities carried out with due regard to health protocol. In addition to counseling also do practice Handwashing with soap and use a Hand Sanitizer appropriate health standards and the distribution of masks to the participants. The activities run smoothly, students better understand the protocol 3 M and procedures for hand washing and use hand sanitizer after extension materials supplied. Community service activities must be done on an ongoing basis, considering the change people's behavior is not easy.